G387 No stone unturned: the epidemiology and outcomes of paediatric urolithiasis in the United Kingdom (2002–2015). (27th April 2016) - Robinson, C; Hennayake, S; Shenoy, M
Abstract : Background: The incidence, aetiology and management of paediatric urolithiasis is changing in developed nations. Since 2003, no authors have characterised the evolving epidemiological patterns of disease in the United Kingdom (UK). Aims: To assess the demographics and presenting features of paediatric urolithiasis, defining the incidence, aetiology, recurrence risk and functional outcomes for those presenting to tertiary urban centres in the UK. Methods: The records of 177 consecutive children (0–18 years) presenting with urolithiasis between Jan. 1, 2002 and April 14, 2015 were prospectively collected for observational analysis. Where possible, children were referred for full metabolic evaluation under the care of our paediatric nephrology unit. Results: The incidence of paediatric urolithiasis, previously unreported in the UK, was found to be 1.77/100, 000 person-years. Incidence was observed to increase significantly over the study period. Patient age at presentation was higher in our series (8.2 years) than that of previous British studies and we observed a declining proportion of males (male:female ratio – 1.3:1) See Figure 1 . The upper urinary tract was most commonly involved: > 90% (upper) vs. 15% (lower). Metabolic abnormalities were identified in 54% of children screened, and 56 cases (32%) were classified as metabolic. The most common abnormalities were hypercalciuria (77%), hyperoxaluria (16%), cystinuria (11%), hypocitraturia (7%). Significant family history was strongly predictive of metabolic aetiologies (OR 5.5:1 vs. no family history). 47% of children had multiple aetiological factors, complicating their investigation and management (see Figure 2 ). Recurrence was described in 31% of children with ≥4 year follow-up. Critically, we report an association between paediatric urolithiasis and adverse long-term renal outcomes. DMSA scans were performed in 55 children; 33 scans were found to be abnormal (60%). Abnormal scans were most common children with both structural anomalies and a history of UTI (88%) but were also seen in those with urolithiasis alone (43%). Conclusions: The incidence of paediatric urolithiasis is rising in the UK, with increasing numbers of females and older children. Metabolic abnormalities commonly underlie stone formation and their recurrence risk is high, justifying the comprehensive screening of all children presenting with urolithiasis.